Pengembangan Pembelajaran Matematika Dengan Menggunakan Model Realistic Mathematics Education Untuk Meningkatkan Kemampuan Pemahaman Konsep Siswa MTs - Utari Prantika Hasibuan; Ellis Mardiana Panggabean (Journal Mathematics Education Sigma [JMES], 2022)
Abstract. The formulation of the problem in this study is: How is the mathematics learning device with the Realistic Mathematics Education model developed by MTs students. This study aims to develop learning tools in the form of lesson plans, teaching materials, LKPD, learning media, and assessment tools based on Realistic Mathematics Education on similarity and congruence materials for grade IX MTs students. The quality of the developed products is assessed based on aspects of validity, practicality, and effectiveness. The procedure for developing learning tools refers to the 4-D development model, namely Define, Design, Develop, and Desseminate. Due to the limitations of the researchers, the research was carried out until it was developed. The subjects of this study were students of class IX-3 MTs Negeri 2 Medan. The instruments used to measure the quality of the learning tools developed were RPP assessment sheets, teaching materials, LKPD, learning media, and assessment tools to measure the validity of these devices. maximum score of 5.00 with good criteria. The average score of teaching materials is 3.73 from a maximum score of 5.00 with good criteria. The average score of LKPD is 3.83 out of a maximum score of 5.00 with good criteria. The average score of learning media is 3.83 out of a maximum score of 5.00 with good criteria, and the average THB score is 3.79 out of a maximum score of 5.00 with good criteria.Abstrak. Rumusan masalah dalam penelitian ini adalah : Bagaimana perangkat pembelajaran matematika dengan model Realistic Mathematics Education hasil pengembangan pada siswa MTs. Penelitian ini bertujuan untuk mengembangkan perangkat pembelajaran berupa RPP, Bahan ajar, LKPD, Media pembelajaran, dan perangkat penilaian berbasis Realistic Mathematics Education pada materi kesebangunan dan kekongruenan untuk siswa MTs kelas IX. Kualitas produk yang dikembangkan dinilai berdasarkan aspek kevalidan, kepraktisan, dan keefektifan. Prosedur Pengembangan perangkat pembelajaran mengacu pada model pengembangan 4-D, yaitu Define (Pendefenisian), Design (Perancangan), Develop (Pengembangan), dan Desseminate (Penyebaran). Karena keterbatasan peneliti, penelitian dilakukan hingga tahan develop. Subjek penelitian ini adalah siswa kelas IX-3 MTs Negeri 2 Medan. Instrumen yang digunakan untuk mengkur kualitas perangkat pembelajaran yang dikembangkan adalah lembar penilaian RPP, Bahan ajar, LKPD, Media pembelajaran, dan Perangkat penilaian untuk mengukur kevalidan perangkat tersebut.Kualitas kevalidan perangkat pembelajaran memenuhi kriteria valid berdasarkan skor rata-rata RPP yaitu 3,85 dari skor maksimal 5,00 dengan kriteria baik. Skor rata- rata bahan ajar yaitu 3,73 dari skor maksimal 5,00 dengan kriteria baik. Skor rata-rata LKPD yaitu 3,83 dari skor maksimal 5,00 dengan kriteria baik. Skor rata- rata media pembelajaran yaitu 3,83 dari skor maksimal 5,00 dengan kriteria baik, dan skor rata-rata THB yaitu 3,79 dari skor maksimal 5,00 dengan kriteria baik.